Existence of Solution for Modified Landau-Lifshitz Model (Journal of Partial Differential Equations, 2005)
In the present paper, the existence of solutions to Cauchy problem for modified Landau-Lifshitz Model initiated by Augusto Visintin is studied.
Keywords: Modified Landau-Lifshitz model; solution; existence